The New Kingdom population on Sai Island: application of Sr Isotopes to investigate cultural entanglement in ancient Nubia - Retzmann, Anika (Ägypten und Levante, 2019)
Sr isotopes were applied to identify possible allochthony of skeletal remains retrieved from Tomb 26 of the pharaonic cemetery SAC5 on Sai Island (Nubia). Tooth enamel of nine individuals, including the Overseer of Goldsmiths Khummose and his presumed ‘wife’, dating from the New Kingdom, were investigated to gain information whether these individuals were first generation immigrants from Egypt (= allochthonous) or members of the local population inhabiting the area of Sai Island (= autochthonous). The interpretation of supposed allochthony and autochthony was based on the comparison of the Sr of human enamel to an assumed autochthonous Sr isotopic composition. The autochthonous Sr signal on Sai Island during the New Kingdom was derived from archaeological animal samples (rodent, sheep/goat, dog and local mollusc shells dating from the New Kingdom) in combination with local environmental samples (paleo sediments dating from the New Kingdom and literature Sr isotope value of Nile River water for the New Kingdom era). As the Sr values in enamel of all individuals investigated lay within the determined autochthonous Sr range on Sai Island during the New Kingdom, all individuals were classified as supposed members of the local population on Sai Island. Elevated Sr, V, Mn and U mass fractions indicated a high degree of post-mortem alterations of human primary dentine. Hence, a mathematical approach was tested in order to correct the Sr isotope ratios in human primary dentine for diagenetic alteration considering a diagenetic Sr proportion and the Sr isotopic composition of the repository material. The rich funerary equipment associated with the burials in Tomb 26 allowed a dating of the family members of Khnummose and illustrated that they belonged to the Egyptian elite on Sai Island as far as their cultural identity is concerned. In combination with the Sr isotopic analysis, Tomb 26 provided fresh information on the complex coexistence and biological and cultural entanglement of Egyptians and Nubians on Sai Island during the New Kingdom.